Performance as a Research Instrument: An Example from the Western European Baroque - Edward C. Van Ness (Institut Seni Indonesia Yogyakarta, 2017)
In this paper, I discuss performance as a research instrument in Western European classical music. I describe considerations and process leading to my performance of Corelli Op. 5 no. 12